Extending UTAUT2 to Examine QRIS Adoption Behavior in Traditional Retail Markets - Rizka Putri Rahayu; Eka Sari Amalia (ICON Publisher, 2026)
The rapid growth of digital payment systems has accelerated the transformation toward a cashless economy in emerging markets, including Indonesia. One of the most widely adopted digital payment innovations is the Quick Response Code Indonesian Standard (QRIS), which has increasingly been implemented in traditional retail markets. This study aims to extend the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) to examine the determinants of behavioral intention and use behavior toward QRIS adoption in traditional retail markets. The study employed a quantitative explanatory approach using survey data collected from QRIS users consisting of traditional retail merchants and consumers. Data were analyzed using Structural Equation Modeling (SEM) to evaluate the relationships among variables. The findings reveal that performance expectancy, effort expectancy, social influence, facilitating conditions, and habit significantly influence behavioral intention toward QRIS adoption. Furthermore, facilitating conditions, habit, and behavioral intention significantly affect actual use behavior. In contrast, hedonic motivation and price value were found to have no significant effect on behavioral intention. The results indicate that QRIS adoption in traditional retail markets is primarily driven by practical utility, ease of use, social encouragement, technological readiness, and habitual behavior rather than emotional enjoyment or economic incentives. This study contributes to the literature on fintech adoption by extending the UTAUT2 framework within the context of digital payment adoption in emerging economies. The findings also provide practical implications for policymakers, fintech providers, and traditional market stakeholders in accelerating digital payment transformation and strengthening financial inclusion.